OLED display : fundamentals and applications - Tsujimura, Takatoshi (Hoboken, N.J. : Wiley, 2012)
This book covers all of the aspects necessary to the design and manufacturing of OLED displays. Topics include emission mechanism, material selection, device processing, manufacturing issues and countermeasures and display design basics. In addition, the book defines elements of OLED such as Thin Film Transistor (TFT) backplane design and processing details, including Low Temperature Poly Silicon (LTPS) process and circuit integration, and high yield method to manufacturer. Researchers and developers are aiming at making large OLED televisions and companies such as Samsung and Apple are rumore.
6.4.1 Performance Target6.4.2 High-Yield Manufacturing by White + Color Filter Method; 6.5 NEXT-GENERATION TFT TECHNOLOGIES FOR OLED DISPLAY; 6.5.1 Sequential Lateral Solidification (SLS) Method; 6.5.2 Microcrystalline and Superamorphous Silicon; 6.5.3 Solid-Phase Crystallization; 6.5.4 Oxide Semiconductors; 7: OLED Lighting; 7.1 COLOR RENDERING INDEX; 7.2 OLED LIGHTING REQUIREMENT; 7.2.1 Correlated Color Temperature (CCT); 7.2.2 Other Requirements; 7.3 LIGHT EXTRACTION ENHANCEMENT; 7.3.1 Microlens Array Structure; 7.3.2 Diffusion Structure; 7.3.3 Diffraction Structure.
Includes bibliographical references and index.
Keywords: Flat panel displays; Electroluminescent devices; Organic semiconductors; Engineering; Electrical engineering; Flat panel displays; Electroluminescent devices; Organic semiconductors; TECHNOLOGY & ENGINEERING -- Electronics -- Circuits -- General; TECHNOLOGY & ENGINEERING -- Electronics -- Circuits -- Integrated; Electroluminescent devices; Flat panel displays; Organic semiconductors; Electronic books